APPLICATION OF PRINCIPAL COMPONENT ANALYSIS METHOD ON TUTOR PERFORMANCE ASSESSMENT INSTRUMENTS WITH JEFFREYS'S AMAZING STATISTICS PROGRAM FORMULA - Ahmad Ahmad (LPPM Universitas Negeri Jakarta, 2022)
Producing tutor performance appraisal instruments is a practical step to improve the quality of human resources and the quality of non-formal education units. This instrument development research aims to produce a standard instrument for assessing tutor performance by involving 250 tutors as respondents when conducting an empirical test by filling in 33 questions representing 11 variables. Data on instrument filling was then analyzed using the formula of Jeffreys's Amazing Statistics Program (JASP) version 16.3. After the instrument met the requirements of factor analysis, an analysis was carried out using the PCA method the results in general the tutor performance assessment instrument had formed eleven main components with various sub-variables of each component such as seven sub-variables, three sub-variables, two sub-variables and one sub variable with matrix values. high correlation, so that the tutor's performance assessment instrument is suitable to be used to assess the tutor's performance.